Preparation of functionalized GO membrane electrode and application of functionalized GO membrane electrode in removal of perfluorinated compounds by coupling alternating current catalysis
Through the application of functionalized graphene oxide membrane electrodes in AC electrochemical systems, the problems of low removal efficiency and high energy consumption of perfluorinated compounds in the existing technology are solved, and efficient and green electrocatalytic degradation effects are achieved.
Patent Information
- Application Number
- CN202411581555.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-11-07
AI Technical Summary
The prior art is difficult to effectively remove perfluoro compounds in water, especially in AC electrochemical systems. There is a lack of enhanced adsorption-catalytic functional membrane electrodes suitable for AC electrochemistry, resulting in low pollutant removal efficiency, high energy consumption and many by-products.
Functionalized graphene oxide (GO) membrane electrode is used, which is dispersed and combined with titanium oxide or highly conductive CNTs materials through ultrasound, followed by reaction under hydrothermal conditions and reaction with imino compounds or quaternary ammonium salts at room temperature. , forming amide bonds to enhance adsorption properties. The membrane electrode serves as the anode in an AC electrochemical system, combined with carbon paper or carbon felt as the cathode, and performs electrocatalytic degradation through circulating electrolyte.
Achine in high efficiency, fast, and green -to -water removal of full fluoride, reducing energy consumption, low degradation products, low toxicity, and no additional drugs, and the process is simple and economic and environmental.
Smart Images

Figure CN119349719A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electrochemical wastewater treatment, and in particular to the preparation of a functionalized GO membrane electrode and its application in coupling alternating current electrocatalysis to remove perfluorinated compounds. Background Art
[0002] Perfluoroalkyl and polyfluoroalkyl substances (PFASs) refer to more than 4,000 fully or highly fluorinated aliphatic chemicals, which are commonly used in the production of fire-fighting materials, lubricants, textiles, cosmetics and herbicides. Due to their unique physical and chemical properties, PFOS and PFOA are widely used at home and abroad. Since 2009, PFOS has been listed as a persistent organic pollutant by the Stockholm Convention and as an emerging pollutant by the US Environmental Protection Agency (EPA). Due to the high fluorine electronegativity, high-strength CF bonds (about 486 kJ / mol) in PFASs molecules and the easy deprotonation of their head groups in water, traditional physical, chemical and biological methods are difficult to effectively remove PFASs. In current research reports, the methods for removing PFASs from water mainly include: adsorption, membrane filtration (nanofiltration, reverse osmosis), plasma, ultrasound, photocatalysis technology, etc. Electrochemical methods can degrade perfluorinated compounds in water, but the removal effect of a single technology is low, there are many by-products, and the risk of secondary pollution is high.
[0003] The patent application document with application number 201910391876.6 discloses a method for degrading perfluorinated compounds in water by electro-oxidation through micro-nano flotation coupled with low-valent titanium oxide electrodes, achieving enrichment followed by oxidation treatment, which greatly increases the degradation effect. However, the electrode material of this method does not have enough adsorption sites, and additional agents need to be added during the early enrichment process. The mass transfer effect of the device is poor, and it is still very challenging in practical applications. Electrocatalytic membrane technology couples the electric field and electrochemical process with the membrane filtration process. The membrane electrode uses the spatial structure of the membrane pores to generate reduction and oxidation active species in situ. The penetration mode enhances the mass transfer effect of pollutants and increases the electron transfer rate. It can quickly, sustainably and thoroughly remove difficult-to-degrade organic pollutants in water. Graphene oxide (GO) can be assembled into GO 2D membranes by simple filtration and other means for use in electrochemical systems. Its huge specific surface area and sp 2 The hybrid structure can greatly improve its ability to adsorb pollutants. Doping elements or co-building nanostructures can significantly improve the generation of active species and diffusion migration at the liquid-solid interface under electric field regulation, further solving the problems of poor electrode adsorption capacity and low catalytic effect.
[0004] At present, the existing electrocatalytic membrane technology research is only used for direct current electrocatalytic systems, and has not yet been found for alternating current electrocatalytic systems. Compared with direct current electrochemistry, in which the positive and negative poles are fixed and only the voltage can be adjusted, alternating current electrochemistry has the characteristics of polarity reversal and periodic fluctuations. In addition to current and voltage, the device parameters can be further adjusted, such as waveform, frequency, duty cycle, etc. At present, international research on the synergistic enhancement of organic pollutant degradation (conversion) by alternating current electrochemical reduction-oxidation has just started, while research on the deep defluorination and mineralization of PFASs is still blank. Therefore, it is urgent to carry out research on the synergistic removal of PFASs based on alternating current electrochemical reduction-oxidation, including the preparation of enhanced adsorption-catalytic functional membrane electrodes suitable for alternating current electrochemistry, and the construction of an alternating current electrochemical treatment system for PFASs based on functional membrane electrodes to improve pollutant removal efficiency and reduce energy consumption. Summary of the invention
[0005] In view of the deficiencies in the prior art, the present invention provides a preparation method of a functionalized GO membrane electrode and an application thereof in coupling alternating current electrocatalysis to remove perfluorinated compounds.
[0006] The specific technical solutions adopted by the present invention are as follows:
[0007] A method for preparing a functionalized GO membrane electrode comprises the following steps:
[0008] 1) subjecting the graphene oxide dispersion to ultrasonic treatment, adding alkali to adjust the pH to alkaline, adding functional reagent 1 to the dispersion to increase the electrode catalytic performance and conductivity, wherein the functional reagent 1 is titanium oxide or a highly conductive CNTs material, and the dispersion is ultrasonically uniform;
[0009] 2) adding the dispersion obtained in step 1) into a reaction kettle, sealing the reaction kettle and transferring it into an oven to perform a hydrothermal reduction reaction to obtain a dispersion of reduced graphene oxide tightly combined with the functional reagent 1;
[0010] 3) adding functional reagent 2 to the dispersion obtained in step 2), wherein the functional reagent 2 is an imino compound or a quaternary ammonium salt, and ultrasonically reacting at room temperature to combine part of the carboxyl groups in the reduced graphene oxide with the amine groups in the functional reagent 2 to form an amide bond, thereby enhancing the adsorption performance and adjusting the membrane spacing;
[0011] 4) The dispersion obtained in step 3) is filtered onto a microfiltration membrane as a support by vacuum filtration, so that the layered structure formed by stacking graphene oxide nanosheets, i.e., the graphene oxide membrane, is fixed on the microfiltration membrane, thereby obtaining the functionalized GO membrane electrode.
[0012] Furthermore, in step 1), the solvent of the graphene oxide dispersion is deionized water, the concentration is 0.5 mg / ml-2 mg / ml, and alkali is added to adjust the pH to 8-12.
[0013] Further, in step 1), the titanium oxide in the functional reagent 1 is Ti 4 O 7 , the mass ratio of graphene oxide to functional reagent 1 is 1-5:1.
[0014] Furthermore, in step 2), the temperature of the hydrothermal reduction reaction is 100-130° C., and the reaction time is 1-3 h.
[0015] Further, in step 3), the functional agent 2 is selected from at least one of polyethyleneimine, hexadecyltrimethylammonium bromide and polyaniline, preferably polyethyleneimine (PEI), with a molecular weight of 25k, and the mass of the functional agent 2 is 2-8%, preferably 4-5% of the mass of the graphene oxide in step 1). The ultrasonic time in step 3) is 2-4h.
[0016] The present invention also provides an application of the functionalized GO membrane electrode coupled with alternating current electrocatalysis to remove perfluorinated compounds, including the construction of an electrochemical system, with the functionalized GO membrane electrode as an anode and carbon paper or carbon felt as a cathode, the anode and cathode are arranged in parallel and spaced apart in an electrolytic cell, and the internal space of the electrolytic cell is divided into three chambers: left, middle and right, the anode and cathode are respectively connected to an AC power source through wires; the liquid outlet of the right chamber is connected to the liquid inlet of the left chamber by a pipeline through a circulation pump, forming a circulating reaction loop; when an electrochemical reaction is carried out, the circulation pump is started to pump out the electrolyte in the right chamber and pass it into the left chamber, and the electrolyte in the left chamber first passes through the anode to enter the middle chamber, and then passes through the cathode to enter the right chamber, forming a circulating circulation of the electrolyte.
[0017] Furthermore, the electrolyte includes a sodium sulfate or sodium bisulfate aqueous solution with a concentration of 0.05-0.2 mol / L as the electrolyte solution, and a perfluorinated compound is added to the electrolyte solution; when performing an electrochemical reaction, the permeation flux of the electrolyte through the anode is 211LMH-473LMH, and the electrolysis reaction time is 60-150min; the negative bias voltage of the AC power supply is -1.6±0.2V, the positive bias voltage is 3.5±0.2V, the duty cycle of the negative bias voltage is 10-50%, and the duty cycle of the positive bias voltage is 50-90%, preferably the duty cycle of the negative bias voltage is 25-30%, and the duty cycle of the positive bias voltage is 70-75%.
[0018] Preferably, the perfluorinated compound is perfluorooctane sulfonic acid (PFOS).
[0019] Furthermore, the frequency of the AC power source is 10-400 Hz, and the concentration of the perfluorinated compound in the electrolyte solution is 50-1000 ppb, preferably 400-600 ppb.
[0020] The beneficial effects of the present invention are:
[0021] 1) The preparation method of the present invention is simple and fast, and no large-scale equipment is required in the preparation process. The good water dispersibility and rich functional groups of graphene oxide are utilized to achieve modification by combining with other elements, nanoparticles, polymers, etc. in a covalent / non-covalent manner, thereby expanding its application range.
[0022] 2) The functionalized GO membrane electrode prepared by the method of the present invention is applied to an AC electrochemical system without the need to add reagents, and the process is simple, economical and environmentally friendly.
[0023] 3) The electrode material of the present invention has good stability and high conductivity, provides a large number of active species for the catalytic degradation process, has low toxicity of the degradation products, and can achieve rapid and efficient degradation of perfluorinated compounds.
[0024] 4) A functionalized GO membrane was prepared as a membrane electrode by vacuum filtration, and an AC electrochemical system coupled with a functionalized GO membrane electrode was established for electrocatalytic degradation of perfluorinated compounds. Compared with the existing DC electrocatalytic technology, the AC electrocatalytic technology can enhance the removal effect of perfluorinated compounds through adsorption-catalytic synergy. The present invention simply modifies graphene oxide to prepare a membrane electrode, and the preparation method is simple and easy; the membrane electrode has good conductivity and a large number of adsorption and catalytic active sites, which are easy to adsorb pollutants and electrocatalytically produce active substances for electrocatalytic degradation of perfluorinated compounds; the AC electrochemical system operates in a penetration mode, the electrode material is stable, and the pollutant mass transfer effect is high; the degradation products have low toxicity, and the degradation process is green and efficient. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 The photos of the functionalized GO membranes provided in Example 1 and Comparative Example 2 of the present invention;
[0026] Figure 2 Comparison results of images of the functionalized GO membranes provided in Example 1 and Comparative Example 2 after being immersed in strong acid and strong base conditions;
[0027] Figure 3 Planar SEM images of the functionalized GO membranes provided in Example 1 of the present invention and Comparative Examples 1 and 2;
[0028] Figure 4 FTIR images of the functionalized GO membranes provided in Example 1 of the present invention and Comparative Examples 1 and 2;
[0029] Figure 5 The effect of different applied voltages on the electrocatalytic degradation of PFOS by functionalized GO membrane;
[0030] Figure 6 The effect of different power sources on the electrocatalytic degradation of PFOS by functionalized GO membrane. DETAILED DESCRIPTION
[0031] The present invention will be further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto.
[0032] In the embodiment of the present invention, the dispersing solvent of the graphene oxide dispersion is water; the graphene oxide prepared by the improved Hummers method, and the CNTs were purchased from Aladdin Bioengineering Co., Ltd.
[0033] Example 1
[0034] In this embodiment, a functionalized GO membrane electrode is prepared, and the preparation method thereof is as follows:
[0035] (1) First, weigh 20 ml of 1 mg / ml graphene oxide dispersion for ultrasonic separation and adjust the pH to 10 with NaOH.
[0036] (2) Add 15 mg of low-valent titanium oxide material Ti to the dispersion 4 O 7 (Functional reagent 1) was added to the reactor after ultrasonication, and the reactor was sealed and placed in an oven. After hydrothermal reduction at 120°C for 1h, rGO-Ti 4 O 7 Dispersion.
[0037] (3) At room temperature, 1 mg of polyethyleneimine (functional reagent 2, molecular weight of polyethyleneimine is 25000, the same below) was added to the dispersion and ultrasonicated for 3 h to finally obtain rGO-PEI-Ti 4 O 7 Dispersion.
[0038] (4) Finally, the dispersion was vacuum filtered through a nylon microfiltration membrane with a diameter of 4.5 cm and a circular structure (the diameter of the effective filtration area of the nylon microfiltration membrane is 4 cm, and its filtration pore size is 0.22 μm). 4 O 7 Store the membrane at room temperature.
[0039] Example 1 rGO-PEI-Ti 4 O 7 For photos of the membrane, see Figure 1 From the sub-figures (a)-(b) in the figure, it can be seen that the film obtained in Example 1 is dark brown, can be bent arbitrarily, has good flexibility and strong stability.
[0040] Example 1 rGO-PEI-Ti 4 O 7 The membrane was soaked in strong acid (pH = 1, hydrochloric acid) for 24 hours, and then the membrane was taken out. Figure 2(a), then placed in a strong base (pH = 12, NaOH solution) and soaked for 24 hours, and then the membrane was taken out. Figure 2 (b) From Figure 2 As can be seen from (a)-(b), the membrane can still maintain its integrity, indicating that the membrane obtained in Example 1 has strong stability.
[0041] Comparative Example 1
[0042] As a comparison with Example 1, a pure rGO membrane was prepared in this comparative example. The preparation method is as follows:
[0043] First, 20 ml of 1 mg / ml graphene oxide dispersion was weighed for ultrasonic separation, and the pH was adjusted to 10 with NaOH. The dispersion was added to the reactor after ultrasonication, and the reactor was sealed and placed in an oven. After hydrothermal reduction at 120°C for 1 hour, the rGO dispersion was obtained. The rGO dispersion was vacuum filtered using a nylon microfiltration membrane with a diameter of 4.5 cm and a circular structure (the diameter of the effective filtration area of the nylon microfiltration membrane is 4 cm, and its filtration pore size is 0.22 μm), and the filtered rGO membrane was stored at room temperature.
[0044] Comparative Example 2
[0045] As a comparison with Example 1, a pure rGO-PEI membrane was prepared in this comparative example. The preparation method is as follows:
[0046] First, 20 ml of 1 mg / ml graphene oxide dispersion was weighed for ultrasonic separation, and the pH was adjusted to 10 with NaOH. The dispersion was added to the reactor after ultrasonic separation, and the reactor was sealed and placed in an oven. After hydrothermal reduction at 120 ° C for 1 h, rGO dispersion was obtained. At room temperature, 1 mg of polyethyleneimine was added to the dispersion and ultrasonicated for 3 h to finally obtain rGO-PEI-Ti 4 O 7 Finally, the dispersion was vacuum filtered through a nylon microfiltration membrane with a diameter of 4.5 cm and a circular structure (the diameter of the effective filtration area of the nylon microfiltration membrane is 4 cm, and its filtration pore size is 0.22 μm), and the filtered rGO-PEI membrane was stored at room temperature.
[0047] The photo of the pure rGO-PEI membrane obtained in Comparative Example 2 is shown in Figure 1 (c), it can be seen that the film is not easy to form.
[0048] Comparative Example 2 The obtained pure rGO-PEI membrane was immersed in a strong acid (pH=1, hydrochloric acid) for 24 hours, then the membrane was taken out and placed in a strong base (pH=12, NaOH solution) for 24 hours, and then the membrane was taken out. Figure 2 (c) It can be seen that after being placed in strong acid and strong base solutions for 24 hours, the integrity of the obtained membrane was destroyed.
[0049] like Figure 3 As shown, they are scanning electron microscope (SEM) images of the membranes of Example 1, Comparative Example 1 and Comparative Example 2, respectively. From the SEM characterization, it can be seen that the surface of the pure rGO membrane obtained in Comparative Example 1 is very smooth, without wrinkles or protrusions, the surface of the pure rGO-PEI membrane obtained in Comparative Example 2 is relatively rough due to the insertion of the modifier, and the surface of the membrane in Example 1 of the present invention becomes rough due to the insertion of the conductive material and the modifier, and a large number of protrusions appear.
[0050] like Figure 4 The FTIR images of the films of Example 1 and Comparative Examples 1 and 2 are shown in FIG. 1 and FIG. 2 respectively show the FTIR images of the functionalized GO films of Example 1 and Comparative Examples 1 and 2. Figure 4 The corresponding results of GTM, rGO and rGO-PEI in Figure 1 confirm that amide bonds are formed between the carboxyl groups from rGO and the amine groups from PEI in the functionalized GO membrane in Example 1.
[0051] Comparative Example 3
[0052] As a comparison with Example 1, rGO-PEI-TiO 2 The preparation method is as follows:
[0053] First, weigh 20 ml of 1 mg / ml graphene oxide dispersion for ultrasonic separation and adjust the pH to 10 with NaOH. Add 15 mg TiO 2 (Functional reagent 1) was added to the reactor after ultrasonication. The reactor was sealed and placed in an oven. After hydrothermal reduction at 120 °C for 1 h, rGO-TiO 2 At room temperature, 1 mg of polyethyleneimine (functional reagent 2) was added to the dispersion and ultrasonicated for 3 h to finally obtain rGO-PEI-TiO 2 Finally, the dispersion was vacuum filtered through a nylon microfiltration membrane with a diameter of 4.5 cm and a circular structure (the diameter of the effective filtration area of the nylon microfiltration membrane is 4 cm, and its filtration pore size is 0.22 μm). 2 Store the membrane at room temperature.
[0054] Comparative Example 4
[0055] As a comparison with Example 1, this comparative example prepared a rGO-PEI-CNTs membrane. The preparation method is as follows:
[0056] First, 20 ml of 1 mg / ml graphene oxide dispersion was weighed for ultrasonic separation, and the pH was adjusted to 10 with NaOH. 15 mg of CNTs material (functional reagent 1) was added to the dispersion, and it was ultrasonically dispersed uniformly and then added to the reactor. The reactor was sealed and placed in an oven. After hydrothermal reduction at 120 ° C for 1 hour, the rGO-CNTs dispersion was obtained. At room temperature, 1 mg of polyethyleneimine (functional reagent 2) was added to the dispersion and ultrasonicated for 3 hours to finally obtain the rGO-PEI-CNTs dispersion. Finally, the dispersion was vacuum filtered with a nylon microfiltration membrane with a diameter of 4.5 cm and a circular structure (the diameter of the effective filtration area of the nylon microfiltration membrane is 4 cm, and its filtration pore size is 0.22 μm), and the filtered rGO-PEI-CNTs membrane was stored at room temperature.
[0057] Comparative Example 5
[0058] As a comparison with Example 1, rGO-CTAB-Ti 4 O 7 The preparation method is as follows:
[0059] First, weigh 20 ml of 1 mg / ml graphene oxide dispersion for ultrasonic separation, and adjust the pH to 10 with NaOH. Add 15 mg of low-valent titanium oxide material Ti to the dispersion. 4 O 7 (Functional reagent 1) was added to the reactor after ultrasonication, and the reactor was sealed and placed in an oven. After hydrothermal reduction at 120°C for 1h, rGO-Ti 4 O 7 At room temperature, 1 mg of hexadecyltrimethylammonium bromide (CTAB) (functional reagent 2) was added to the dispersion and ultrasonicated for 3 h to finally obtain rGO-CTAB-Ti 4 O 7 Finally, the dispersion was vacuum filtered through a nylon microfiltration membrane with a diameter of 4.5 cm and a circular structure (the diameter of the effective filtration area of the nylon microfiltration membrane is 4 cm, and its filtration pore size is 0.22 μm). 4 O 7 Store the membrane at room temperature.
[0060] Comparative Example 6
[0061] As a comparison with Example 1, rGO-PANI-Ti 4 O 7 The preparation method is as follows:
[0062] First, weigh 20 ml of 1 mg / ml graphene oxide dispersion for ultrasonic separation, and adjust the pH to 10 with NaOH. Add 15 mg of low-valent titanium oxide material Ti to the dispersion.4 O 7 (Functional reagent 1) was added to the reactor after ultrasonication, and the reactor was sealed and placed in an oven. After hydrothermal reduction at 120°C for 1h, rGO-Ti 4 O 7 At room temperature, 1 mg of polyaniline (PANI) (functional reagent 2) was added to the dispersion and ultrasonicated for 3 h to finally obtain rGO-PANI-Ti 4 O 7 Finally, the dispersion was vacuum filtered through a nylon microfiltration membrane with a diameter of 4.5 cm and a circular structure (the diameter of the effective filtration area of the nylon microfiltration membrane is 4 cm, and its filtration pore size is 0.22 μm). 4 O 7 Store the membrane at room temperature.
[0063] Example 2
[0064] The functionalized GO membranes prepared in Example 1 and the comparative examples were subjected to permeation flux tests. The specific method is as follows: the volume of water passing through a unit membrane area per unit time under unit pressure is used to determine the permeability of the membrane. Water flux J (L·m -2 ·h -1 bar -1 ) is calculated by the following formula:
[0065] J=V / (t*A*P)
[0066] Where A is the effective membrane area (m 2 ), V is the volume of filtered liquid (L), t is the filtering time (h), and P is the applied pressure (bar). The specific results are shown in Table 1.
[0067] As shown in Table 1, rGO-PEI-Ti 4 O 7 The membrane exhibited the highest permeate flux relative to other membranes.
[0068] Example 3
[0069] The modified graphene oxide membrane electrodes prepared in Example 1 and the comparative examples were used for electrocatalytic degradation of perfluorinated compounds. The degradation rate calculation formula of the modified graphene oxide membrane electrode for degradation of perfluorinated compounds is as follows:
[0070] η=(S 0 -S) / S 0 *100%
[0071] Where: S 0 represents the peak area of the perfluorinated compound before degradation, and S represents the peak area of the perfluorinated compound after degradation. The peak area can be measured by liquid chromatography-mass spectrometry.
[0072] 1. Effect of different anode materials on the electrocatalytic degradation of perfluorinated compounds by functionalized GO membrane.
[0073] A circular carbon paper with a diameter of 2.5 cm is used as the cathode, and a circular GO membrane with different functionalizations with a diameter of 2.5 cm is used as the anode. The cathode, anode and reaction tank are sealed with gaskets and fixed with bolts. The anode and cathode divide the internal space of the reaction tank into three chambers: left, middle and right. The anode and cathode are connected to a DC power supply through wires, respectively. The liquid outlet of the right chamber is connected to the liquid inlet of the left chamber through a circulating pump by a pipeline to form a circulating reaction loop. In the reaction tank, 0.1 mol / L Na containing 500 ppb PFOS is used. 2 SO 4 The solution was used as an electrolyte solution, the pH of the electrolyte solution was adjusted to 8, and the volume of the electrolyte solution was 60 mL.
[0074] When the electrochemical reaction is carried out, the circulation pump is started to pump the electrolyte in the right chamber out and into the left chamber. The electrolyte in the left chamber first passes through the anode into the middle chamber and then passes through the cathode into the right chamber, forming a circulation of the electrolyte.
[0075] When an anode material is used, the electrolyte permeation flux through the anode is controlled to be constant at 211LMH, and the electrocatalytic reaction is carried out at a voltage of 3.5V. The electrolysis results are tested when the electrolysis time is 120min. After sampling and adding the internal standard M8PFOS, the sample is tested by LC-MS to calculate the degradation rate of PFOS. The PFOS removal rate results after 120min of electrocatalysis are summarized in Table 1.
[0076] Table 1 Comparison of different anode materials
[0077]
[0078] In Comparative Example 1, the membrane permeation flux of the pure rGO membrane is too small and the catalytic performance is poor, so the electrocatalytic degradation experiment cannot be carried out well.
[0079] 2. Effect of applied DC voltage on the electrocatalytic degradation of perfluorinated compounds by functionalized GO membrane.
[0080] Using rGO-PEI-Ti of Example 1 4 O 7The membrane was used as the anode, and the test conditions of step 1 of Example 3 were repeated to carry out the electrocatalytic test, changing the voltage conditions and the sampling and analysis time, while the other conditions remained unchanged. When the voltage was controlled to be -1.6V, -1V, 0V, 1.5V, 3.5V and 4.5V, samples were taken at 30min, 60min and 120min of electrocatalysis, respectively, and the samples were tested by LC-MS after adding the internal standard M8PFOS, and the degradation rate of PFOS was calculated. The test results are shown in Figure 5 .
[0081] like Figure 5 , thus determining that the preferred bias voltages of the present invention are 3.5V and -1.6V.
[0082] 3. Effect of initial concentration on the electrocatalytic degradation of perfluorinated compounds by functionalized GO membrane.
[0083] Using rGO-PEI-Ti of Example 1 4 O 7 The membrane was used as an anode, and the test conditions of step 1 of Example 3 were repeated to perform an electrocatalytic test, and the initial concentration of PFOS in the electrolyte solution was changed to 50 ppb, 200 ppb, 500 ppb or 1000 ppb, and the other conditions remained unchanged. The control voltage was 3.5 V, the electrolysis time was 120 min, and the degradation rate of PFOS was shown in Table 2.
[0084] As shown in Table 2, it is determined that the preferred initial concentration of pollutants in the present invention is 500 ppb.
[0085] Table 2 Effect of different initial concentrations on PFOS removal rate
[0086]
[0087] 4. Effect of different power sources on the electrocatalytic degradation of perfluorinated compounds by modified graphene oxide membrane.
[0088] Using rGO-PEI-Ti of Example 1 4 O 7 The membrane was used as the anode, and the test conditions of step 1 of Example 3 were repeated for electrocatalytic test. The DC voltage was controlled to 3.5 V. Samples were taken for analysis at 30 min, 60 min and 120 min of electrocatalysis. After adding the internal standard M8PFOS, the samples were tested by LC-MS to calculate the degradation rate of PFOS. The test results are shown in Figure 6 The line curve corresponding to the DC power supply in.
[0089] Using rGO-PEI-Ti of Example 1 4 O 7The membrane was used as the anode, and the test conditions of step 1 of Example 3 were repeated for electrocatalytic test, except that "the DC power supply was replaced by an AC power supply, the negative bias and positive bias of the AC power supply were -1 V and 3.5 V, respectively, the negative bias duty cycle was 25%, the positive bias duty cycle was 75%, and the frequency was 400 Hz", and the other conditions remained unchanged. Samples were taken for analysis at 30 min, 60 min, and 120 min of electrocatalysis, and the samples were tested by LC-MS after adding the internal standard M8PFOS, and the degradation rate of PFOS was calculated. The test results are shown in Figure 6 The line curve corresponding to the AC power supply in.
[0090] like Figure 6 , thus determining that the AC power supply device of the present invention has a higher degradation rate for PFOS, with a removal rate of 87.69%.
[0091] The contents described in this specification are merely an enumeration of implementation forms of the inventive concept, and the protection scope of the present invention should not be regarded as being limited to the specific forms described in the embodiments.
Claims
1. A method for preparing a functionalized GO membrane electrode, characterized in that The following steps are involved: 1) ultrasonically treating a graphene oxide dispersion, adding alkali to adjust the pH to alkaline, adding a functional reagent 1 to the dispersion to increase the electrode catalytic performance and conductivity, wherein the functional reagent 1 is titanium oxide or a highly conductive CNTs material, and the dispersion is ultrasonically uniform; 2) The dispersion obtained in step 1) is added to a reaction kettle, which is sealed and then transferred to an oven for hydrothermal reduction reaction to obtain a dispersion of reduced graphene oxide tightly combined with the functional reagent 1; 3) Adding functional reagent 2 to the obtained dispersion in step 2), wherein the functional reagent 2 is an imino compound or a quaternary ammonium salt, and ultrasonically reacting at room temperature to combine part of the carboxyl groups in the reduced graphene oxide with the amine groups in the functional reagent 2 to form an amide bond, thereby enhancing the adsorption performance and adjusting the membrane spacing; 4) The dispersion obtained in step 3) is filtered onto a microfiltration membrane as a support by vacuum filtration, so that the layered structure formed by stacking graphene oxide nanosheets, i.e., the graphene oxide membrane, is fixed on the microfiltration membrane, thereby obtaining the functionalized GO membrane electrode.
2. The method for preparing a functionalized GO membrane electrode according to claim 1, characterized in that In step 1), the concentration of the graphene oxide dispersion is 0.5 mg / ml-2 mg / ml, and alkali is added to adjust the pH to 8-12.
3. The method for preparing a functionalized GO membrane electrode according to claim 1, characterized in that In step 1), the functional agent 1 is a low-valent titanium oxide, the low-valent titanium oxide is selected from Ti4O7, and the mass ratio of graphene oxide to the functional agent 1 is 1-5:
1.
4. The method for preparing a functionalized GO membrane electrode according to claim 1, characterized in that In step 2), the temperature of the hydrothermal reduction reaction is 100-130° C., and the reaction time is 1-3 h.
5. The method for preparing a functionalized GO membrane electrode according to claim 1, characterized in that In step 3), the functional reagent 2 is selected from at least one of polyethyleneimine, hexadecyltrimethylammonium bromide and polyaniline, preferably polyethyleneimine, and the mass of the functional reagent 2 is 2-8%, preferably 4-5% of the mass of the graphene oxide in step 1); the ultrasonic time in step 3) is 2-4h.
6. A functionalized GO membrane electrode prepared as described in any one of claims 1-5.
7. Use of a functionalized GO membrane electrode coupled with alternating current electrocatalysis to remove perfluorinated compounds as claimed in claim 6.
8. The use according to claim 7, characterized in that The invention comprises the construction of an electrochemical system, wherein the functionalized GO membrane electrode is used as an anode, and carbon paper or carbon felt is used as a cathode. The anode and the cathode are arranged in parallel and spaced apart in an electrolytic cell, and the internal space of the electrolytic cell is divided into three chambers: left, middle and right. The anode and the cathode are respectively connected to an AC power source through a wire; the liquid outlet of the right chamber is connected to the liquid inlet of the left chamber through a pipeline through a circulation pump, so as to form a circulation reaction loop; when an electrochemical reaction is carried out, the circulation pump is started to pump out the electrolyte in the right chamber and pass it into the left chamber, and the electrolyte in the left chamber first passes through the anode to enter the middle chamber, and then passes through the cathode to enter the right chamber, so as to form a circulation of the electrolyte.
9. The use according to claim 8, characterized in that The electrolyte comprises an aqueous solution of sodium sulfate or sodium bisulfate with a concentration of 0.05-0.2 mol / L as the electrolyte solution, and a perfluorinated compound is added to the electrolyte solution; when performing an electrochemical reaction, the permeation flux of the electrolyte through the anode is 211 LMH-473 LMH, and the electrolysis reaction time is 60-150 min; the negative bias voltage of the AC power supply is -1.6±0.2 V, the positive bias voltage is 3.5±0.2 V, the duty cycle of the negative bias voltage is 10-50%, and the duty cycle of the positive bias voltage is 50-90%, preferably the duty cycle of the negative bias voltage is 25-30%, and the duty cycle of the positive bias voltage is 70-75%.
10. The use according to claim 8, characterized in that The frequency of the AC power source is 10-400 Hz, and the concentration of the perfluorinated compound in the electrolyte solution is 50-1000 ppb, preferably 400-600 ppb.
Citation Information
Patent Citations
Method for removing perfluorinated compounds (PFCs) in wastewater through micro-nano gas-floating coupled electrooxidation device
CN110342728A
Graphene / PEI (polyethyleneimine) gas barrier composite membrane and preparing method of graphene / PEI gas barrier composite membrane
CN105038222A
Carbon nanotube / graphene composite gel and preparation method thereof
CN105590757A
Graphene-polyaniline nanoparticle composite film electrode and preparation method thereof
CN105788880A
Electrocatalysis membrane filter device and preparation method of electrocatalysis filtration membrane of device
CN108543423A
Cited By
Method for degrading PFAS in wastewater by using alternating current technology
CN120504371A
A method for degrading pfas in wastewater using alternating current technology
CN120504371B